Model Pembelajaran Discovery Learning, Pemahaman Konsep Biologi, dan Sikap Ilmiah Peserta Didik - Patrianingsih, Endang Ayu; Kaseng, Ernawati S. (Indonesian Journal of Educational Studies, 2016)
This study aimed to describe the application of learning and discovery learning model influence on the understanding of the concept of Biology and learners' scientific attitude. This research is a quasi-experimental research with non-equivalence experimental design pretest posttes control group design. The study population was all study groups is students of Â SMA Negeri 3 Takalar 2015/2016 academic year. Samples were taken by simple random sampling technique. Data were collected using a multiple choice test and questionnaire reasoned scientific attitude. Data were analyzed with descriptive analysis and MANOVA test. The results showed: (1) understanding the concept of Biology students that learned with discovery learning model low category learning and scientific attitude is very good category; (2) understanding the concept of Bilogy students that learned by direct learning model of instruction category is very low and the scientific attitude either category; (3) there are differences in understanding of the concept of Biology significantly among learners that learned learning model discovery learning and direct instruction; (4) there is a scientific attitude of students that learned learning model discovery learning and direct instruction; and (5) there are differences in understanding of biology concepts and scientific attitudes among learners that learned discovery learning and direct instruction.